2002
DOI: 10.1081/ese-120002582
|View full text |Cite
|
Sign up to set email alerts
|

Filtration Treatment of Dairy Processing Wastewater

Abstract: The effectiveness of various filtration agents in the primary treatment of dairy processing wastewater was investigated in laboratory-scale studies. The filtration agents used were: zeolite, crushed coral, charcoal, sand and crushed coral and sand and glass beads. The effectiveness of the filtration media was determined by testing parameters such as chemical oxygen demand (COD), total solids (TS) and total suspended solids (TSS) before and after filtration of wastewater. Percent reduction of the different para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Nevertheless, the decrease in COD removal does indicate partial zeolite saturation. The ability of zeolites to absorb organic matter has been previously reported in various studies [17,18,39]. Kolakovic et al [17] reported that COD reduction from dairy wastewater using organozeolite and a filter column ranged from 30% to 50% when a mean initial COD concentration of 2676 mg/L was applied.…”
Section: Sorption Column Studies Using Scwmentioning
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, the decrease in COD removal does indicate partial zeolite saturation. The ability of zeolites to absorb organic matter has been previously reported in various studies [17,18,39]. Kolakovic et al [17] reported that COD reduction from dairy wastewater using organozeolite and a filter column ranged from 30% to 50% when a mean initial COD concentration of 2676 mg/L was applied.…”
Section: Sorption Column Studies Using Scwmentioning
confidence: 88%
“…Nevertheless, the exact mechanism of COD removal was not examined by Kolakovic et al [17] and was attributed to the zeolite's ability to absorb both organic and inorganic substances. Samkutty and Gough [18] reported higher COD removal (76%) when applying dairy processing wastewater with low initial COD concentrations (between 713 and 1410 mg/L), however provided no data on the zeolite used. High COD removal (71.8%) was also recorded by Guo et al [48], however this research studied the treatment of swine wastewater using a composite of MgO-modified zeolite and a bioflocculant rather than a natural zeolite.…”
Section: Sorption Column Studies Using Scwmentioning
confidence: 99%
See 2 more Smart Citations
“…Charcoal is such a material and it is ubiquitously available in Uganda. The use of charcoal for wastewater treatment has been widely studied (Abe et al, 1993;Samkutty and Gough, 2002;Scholz and Xu, 2002;Ochieng et al, 2004;Sirianuntapiboon et al, 2007;Nkwonta et al, 2010;Ahamad and Jawed, 2011). Its performance compared well with other media like gravel, sand rocks and zeolite, however, attaining its continued use is still a challenge.…”
Section: Introductionmentioning
confidence: 99%